Increased Mitochondrial DNA Copy Number and Oxidative Damage in Patients with Hashimoto's Thyroiditis - Fatemeh Esfahanian; Mojgan Mirabdolhagh Hazaveh; Laya Hooshmand Garehbagh; Kowsar Falahati; Mitra Ataei; Mohammad Hossein Sanati; Zohreh Jadali (Tehran University of Medical Sciences, 2021)
Background: The purpose of present study was to investigate mitochondrial DNA copy number (mtDNAcn) and mtDNA damage in peripheral blood of patients with Hashimoto's thyroiditis (HT) and healthy controls (HC). Methods: The relative mtDNAcn and oxidative DNA damage in this case-control study were measured in peripheral blood of 50 patients with Hashimoto's thyroiditis and 50 healthy controls using quantitative real-time PCR. The study was conducted in Tehran University of Medical Sciences hospital, Tehran, Iran in 2018. Results: HT patients had significantly higher mitochondrial DNA copy number and mitochondrial oxidative damage than the comparison group. Conclusion: These data suggest the possible involvement of mitochondria and oxidative stress in the pathophysiology of HT.